2004
DOI: 10.1111/j.1467-7652.2004.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced levels of methionine and cysteine in transgenic alfalfa (Medicago sativaL.) plants over‐expressing theArabidopsiscystathionine γ‐synthase gene

Abstract: SummaryWith the aim of increasing the methionine level in alfalfa ( Medicago sativa L.) and thus improving its nutritional quality, we produced transgenic alfalfa plants that expressed the Arabidopsis cystathionine γ -synthase (AtCGS), the enzyme that controls the synthesis of the first intermediate metabolite in the methionine pathway. The At CGS cDNA was driven by the Arabidopsis rubisco small subunit promoter to obtain expression in leaves. Thirty transgenic plants were examined for the transgene protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 34 publications
1
36
0
1
Order By: Relevance
“…These transgenic tobacco plants also exhibited increased tolerance to cadmium presumably due to induction of antioxidant enzymes (Ning et al 2010). Recently, Avraham et al (2005) reported enhanced levels of methionine and cysteine in transgenic alfalfa, a forage crop, by overexpressing Arabidopsis cystathionine c-synthase gene. Importantly, they observed 2.6-and 2.3-fold increases in the levels of free and proteinbound cysteine content, respectively, in these transgenic alfalfa plants.…”
Section: Discussionmentioning
confidence: 97%
“…These transgenic tobacco plants also exhibited increased tolerance to cadmium presumably due to induction of antioxidant enzymes (Ning et al 2010). Recently, Avraham et al (2005) reported enhanced levels of methionine and cysteine in transgenic alfalfa, a forage crop, by overexpressing Arabidopsis cystathionine c-synthase gene. Importantly, they observed 2.6-and 2.3-fold increases in the levels of free and proteinbound cysteine content, respectively, in these transgenic alfalfa plants.…”
Section: Discussionmentioning
confidence: 97%
“…Bellucci et al (2002) and Bagga et al (2004) used endosperm storage protein (zein) of maize, usually rumen-protected and rich in the essential sulfur containing amino acids, to stably express it in alfalfa produced. The transgenic alfalfa plants expressing Arabidopsis cystathionine γ-synthase (AtCGS) showed up to 32-fold, 19-fold, and 2.2-fold increase in the total methionine, S-methylmethionine (SMM), and methionine content of the water-soluble proteins, respectively (Avraham et al 2004). Thus transgenic alfalfa plants with significantly higher levels of methionine and cysteine present promising strategy to improve protein quality.…”
Section: Protein Quality and Utilizationmentioning
confidence: 99%
“…However, a reduction in TS activity in potato caused a far stronger molar increase in methionine levels than the molar decrease in threonine level (Zeh et al, 2001). In addition, in the mto1 Arabidopsis mutant as well as in transgenic tobacco, alfalfa and Arabidopsis plants in which the CGS was overexpressed, significant increases in methionine levels were not accompanied by significant changes in threonine levels (Inba et al, 1994;Gakiere et al, 2000a;Hacham et al, 2002;Kim et al, 2002;Avraham et al, 2005). Moreover, Arabidopsis plants expressing the antisense form of CGS showed a significant increase in OPH level ($21-fold), while threonine was increased only $4-fold (Gakiere et al, 2000b).…”
Section: Introductionmentioning
confidence: 94%